The influeance of consumers perception of green product on green purchase intention among students UiTM Melaka / Muhammad Hamdan - Muhammad Hamdan (Faculty of Business and Management, 2017)
This paper to explore the factors that contribute to influence of consumer perception of green product on green purchase intention among student UiTM Melaka City Campus. Sample random sampling are been use in this study.189 respondent have been answer the questionnaire by the respondent. The questionnaire has been distributed to UiTM Melaka City Campus student from semester four and semester five during a weekdays. There are five independent variable for this study which are green packaging, green product value, eco-label, green corporate perception and lastly green advertisement. Thus, the result of the study show the most influential green purchase intention is green corporate perception.